Consider the infinite series $\; \displaystyle \sum_{n=0}^{\infty} \left(\frac{1}{ 4}\right)^{\!n/2}.$

Find the sum of this series.

Formula for calculating sum of the series is:

$$\frac{a}{1 - r}$$

Where Riemann sum must either look as:

$\sum_{n=0}^{\infty} a \cdot r^n\;\;$ or $\;\;\; \sum_{n=1}^{\infty} a \cdot r^{n-1}$

So one way to figure out this problem is to rewrite the given Riemann sum as two sums, one for even and the other for odd n.

Edit: Kind of like this:

$\sum (\frac{1}{4})^n + \sum \frac{1}{2} \cdot (\frac{1}{4})^{\frac{2n}{2}} $

For even, standard is 2k, for odd just simply 2k + 1.

In my case there's fraction involved in the exponent, so I get:

$\sum (\frac{1}{4})^{2n}{2} + \sum (\frac{1}{4})^{ \frac{2n +1}{2}}$ ->

$\sum (\frac{1}{4})^{2n}{2} + \sum (\frac{1}{4})^{ \frac{2n}{2} + \frac{1}{2}}$ ->

$\sum (\frac{1}{4})^n + \sum (\frac{1}{4})^{ \frac{2n}{2}} \cdot (\frac{1}{4})^{ \frac{1}{2}} $

  • 1
    $\begingroup$ Why not just rewrite $(1/4)^{n/2} = (1/2)^n$? $\endgroup$ – Antonio Vargas Oct 21 '15 at 5:48

Alternately use index laws:

$$\sum_{n=0}^{\infty} \left(\frac{1}{ 4}\right)^{\frac{n}{2}}=\sum_{n=0}^{\infty} \left(\left(\frac{1}{ 4}\right)^{\frac{1}{2}}\right)^n$$ $$=\sum_{n=0}^{\infty} \left(\frac{1}{2}\right)^n$$


I think it is $$\sum (\frac{1}{4})^{\frac{n}{2}}=\sum (\frac{1}{4})^{\frac{2n}{2}}+\sum (\frac{1}{4})^{\frac{2n+1}{2}}=\sum (\frac{1}{4})^{\frac{2n}{2}}+\sum (\frac{1}{4})^{\frac{2n}{2}}\times \frac{1}{2}$$


Hint: $$\sum_{n=0}^{\infty} \left(\frac{1}{ 4}\right)^{\!n/2}=(1/4)^{n/2} = 1/2^n$$ Now just use the sum to infinite geometric series.

  • $\begingroup$ I don't need "hint", show me the steps how you got to (1/2)^n $\endgroup$ – Jack Oct 21 '15 at 5:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.